Social Justice Education in an Urban Charter Montessori School - Banks, Kira; Maixner, R. Alex (Journal of Montessori Research, 2016)
As the Montessori Method continues its expansion in public education, a social justice lens is needed to analyze its contributions and limitations, given the increase in racial and socioeconomic diversity in the United States. Furthermore, much of the work in Social Justice Education (SJE) focuses on classroom techniques and curriculum, overlooking the essential work of school administrators and parents, whose work significantly influences the school community. The current study applied an SJE framework to the efforts of one urban, socioeconomically and racially integrated Montessori charter school. We examined the extent to which SJE principles were incorporated across the school community, using an inductive, qualitative, case-study approach that included meetings, surveys, focus groups, and interviews. Administrators quickly adopted a system-wide approach, but parents—often color-blind or minimizing of the relevance of race—consistently resisted. Study results imply a continued need for an institutional approach, not solely a classroom or curricular focus, when integrating social justice into Montessori schools.